Micro-doppler radar and its applications - Fioranelli, Francesco; Griffiths, H. 1956-; Ritchie, Matthew; Balleri, Alessio (The Institution of Engineering and Technology, 2020)
This book covers the latest developments in radar micro-Doppler signatures and noncooperative recognition of moving targets, for researchers and advanced students of radar systems. Micro-Doppler signatures is a very broad topic with applications in healthcare, security and surveillance. Edited by leading researchers in the field, the book consists of a series of chapters with contributions from different groups of authors who are international experts on their topics. The following topics are covered: multistatic radar micro-Doppler; passive radar approaches for healthcare; sparsity-driven methods for micro-Doppler detection and classification; deep neural networks for radar micro-Doppler signature classification; classification of personnel for ground-based surveillance; multimodal sensing for assisted living using radar; micro-Doppler analysis of ballistic targets; small drones and bird signatures as emerging targets; hardware development and applications of portable FMCW radars; digital-IF CW Doppler radar and its contactless healthcare sensing; L1-norm principal component and discriminant analyses of micro-Doppler signatures for indoor human activity recognition; and micro-Doppler signature extraction and analysis for automotive application. Finally, the editors have written a concluding short chapter that brings together an overview of the field and discusses likely future trends.